Inovasi Digital: Implementasi Mini Photobox sebagai Alat Pemasaran Kreatif untuk UMKM - Oktaviani Arcici Hadir; Maharani Ikaningtyas (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
In the digital era, consumers increasingly rely on the internet to buy products or search for information. Therefore, MSME that do not utilize digital technology may miss the opportunity to expand their markets and increase their competitiveness. One of the main challenges faced by MSMEs is the quality of product photos. A mini photobox is a device or tool specifically designed to help MSME (Micro, Small and Medium Enterprises) take photos of their products with high quality results. By using a mini photobox, product photos become brighter, the details clearer, and the colors more accurate. Mini photoboxes help help products stand out more in photos and make them easier to edit or crop for marketing purposes.